MUC16: molecular analysis and its functional implications in benign and malignant conditions. Issue 10 (2nd July 2014) - Haridas, Dhanya; Ponnusamy, Moorthy P.; Chugh, Seema; Lakshmanan, Imayavaramban; Seshacharyulu, Parthasarathy; Batra, Surinder K.
Abstract : MUC16 is a high‐molecular‐weight glycoprotein that is expressed by the various epithelial cell surfaces of the human body to protect the cell layer from a myriad of insults. It is the largest mucin known to date, with an 22, 152 aa sequence. Structurally, MUC16 is characterized into 3 distinct domains: the amino terminal, the tandem repeat, and the carboxyl terminal domain, with each domain having unique attributes. The extracellular portion of MUC16 is shed into the bloodstream and serves as a biomarker for diagnosing and monitoring patients with cancer; however, its functional role in cancer is yet to be elucidated. Several factors contribute to this challenge, which include the large protein size; the extensive glycosylation that the protein undergoes, which confers functional heterogeneity; lack of specific antibodies that detect the unique domains of MUC16; and the existence of splicing variants. Despite these limitations, MUC16 has been established as a molecule of significant application in cancer. Hence, in this review, we discuss the various aspects of MUC16, which include its discovery, structure, and biological significance both in benign and malignant conditions with an attempt to dissect its functional relevance.— Haridas, D., Ponnusamy, M. P., Chugh, S., Lakshmanan, I., Seshacharyulu, P., and Batra, S. K., MUC16: molecular analysis and its functional implications in benign and malignant conditions. FASEB J. 28, 4183‐4199 (2014). www.fasebj.org